Motivations for donating and attitudes toward screening policies in US blood donors with viral infection. Issue 8 (28th June 2016) - Vahidnia, Farnaz; Stramer, Susan L.; Kessler, Debra; Gonçalez, Thelma T.; Shaz, Beth H.; Leparc, German; Krysztof, David E.; Dodd, Roger Y.; Glynn, Simone A.; Custer, Brian; ,
Abstract : BACKGROUND: Differences in motivating factors that contribute to the decision to donate blood between infected and uninfected donors may help to identify areas for improving donor education. STUDY DESIGN AND METHODS: As part of a risk factor study, confirmed‐positive donors (cases) based on serology‐only (human T‐lymphotropic virus [HTLV]) or serology and nucleic acid testing (NAT) or NAT‐only (human immunodeficiency virus [HIV], hepatitis B virus [HBV], hepatitis C virus [HCV]), and serology‐unconfirmed, NAT‐negative false‐positive donors (controls) were asked about motivations and opinions toward blood donation. "Test seeking" was inferred if a donor answered "yes" to "I wanted to get my test results" and one of the following: "blood center testing is confidential, " "free, " "more accurate than other test centers, " or "tests will identify problems with my blood." Cases were compared to controls using descriptive and multivariable analyses. RESULTS: Whether a case or control, the most common donation reason was "to help someone in need" (>90% in each group). After adjusting for demographic characteristics, test seeking was not significantly associated with infection status. Test seeking was more common in first‐time, younger males and nonwhite, non‐Hispanic donors. Of donors with HIV, 13% considered selection policies to be unfair, compared with 1, 2, 0.5, and 6% of donors with HBV, HCV, and HTLV and controls, respectively (adjusted odds ratio for HIV cases vs. controls, 3.9; 95% confidence interval, 2.3‐6.7). CONCLUSIONS: Most donors give to help those in need, including HIV‐positive donors. Our results establish a baseline from which additional studies can be compared focused on alternate ways to reduce noncompliance and improved messaging to ensure that high‐risk potential donors understand the reasons for blood donor screening policies.